PENGARUH GROWTH DALAM RELASI PROFITABILKITAS DAN LIKUIDITAS DENGAN KEBIJAKAN DIVIDEN - Samuel Horas Sarjana (Jurnal Akuntansi dan Perpajakan Jayakarta, 2019)
The research aimed to examine : 1) the influence of Profitability on Dividend Policy, 2) the influence of Liquidity on Dividend Policy, 3) the influence of Growth in relation between Profitability and Dividend Policy, 4) the influence of Growth in relation between Liquidity and Dividend Policy. This research used Growth as moderating variable. The results of this research are: 1) Profitability proxied by ROA partially have positive and significant effect on Dividend Policy, 2) Liquidity proxyed with Cash From Operation partially has no effect on Dividend Policy, 3) Growth proxied with Asset growth is partially able to influence the relationship Profitability and Dividend Policy and 4) Growth proxied with Asset Growth partially unable to influence the relationship Cash Flow Operations and Dividend Policy. While simultaneously independent variables and moderation have an effect on significant to Dividend Policy